2012
DOI: 10.1007/s11743-012-1383-7
|View full text |Cite
|
Sign up to set email alerts
|

Real Time Study of Detergent Concentration Influence on Solid Fatty Acid Film Removal Processes

Abstract: International audienceCleaning in an aqueous solution is a complex mechanism which depends on several parameters. The quartz crystal microbalance (QCM) technique was used to investigate the detachment, using an anionic and a nonionic detergents, of stearic acid (C18H36O2) films deposited on gold-coated quartz surfaces. The cleaning mechanism was observed in real time by measuring the frequency of a quartz crystal during the fatty acid film removal. These observations reveal two successive phenomena: firstly, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…In this study, from a practical viewpoint of detergency, the soil removal was observed immediately after the moment when the soiled substrate was immersed into the detergent solution from atmosphere, as reported by Favrat et al [20].…”
Section: Cleaning Testmentioning
confidence: 72%
See 2 more Smart Citations
“…In this study, from a practical viewpoint of detergency, the soil removal was observed immediately after the moment when the soiled substrate was immersed into the detergent solution from atmosphere, as reported by Favrat et al [20].…”
Section: Cleaning Testmentioning
confidence: 72%
“…Other researchers [16][17][18][19] have recorded the QCM frequency after injecting a given amount of the concentrated detergent solution into a bath of ultrapure water, which enables to observe the effect of the detergent by switching the bath liquid from water to detergent solution. In this study, from a practical viewpoint of detergency, the soil removal was observed immediately after the moment when the soiled substrate was immersed into the detergent solution from atmosphere, as reported by Favrat et al [20].…”
Section: Cleaning Testmentioning
confidence: 72%
See 1 more Smart Citation
“…Other research has evaluated extremely sensitive instrumentation for detecting deposit formation and removal on the nano lengths scale. Chen et al, (2010) and Favrat et al, (2012) used a quartz crystal microbalance (QCM) which allows for real time determination of nano-gram amounts of deposit on various substrates determined by changes in vibrational properties of the substrate itself.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…In order to analyze the mechanism of oily soil removal during washing, many studies have been conducted by applying various methods such as molecular dynamics simulations 22 , combined molecular dynamics and quantum mechanics 23 , lattice Monte Carlo simulations 24 , confocal laser scanning microscopy 25 , a scanning fluid dynamic gauging device 26 , and the quartz crystal microbalance technique 27 .…”
Section: Introductionmentioning
confidence: 99%